Prototype of Mobile Meter Waveband Radar with Improved Functionality - I. S. Sadovskiy; Y. Y. Bobkov; I. Y. Malevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Actual stage of meter waveband radar evolution is the design of mobile radar with improved surveillance functions, as well as signal generation and processing. Such radars measure coordinates of aircraft in 3D space with adaptive change of operation frequency, parameters of probing signal, and polarization. Except radiolocation tasks, such radars allow to carry out integral information processing, EM analysis, ELINT, as well as jamming and clutter canceling, and must have height mobility and secrecy properties. The achievement of these properties is possible due to the application of digital antenna arrays with digital solid-state Tx/Rx modules, modular construction of all radar subsystems, digital beamforming technology, adoptive algorithms of space-time, and statistical processing of received signals. The prototype of meter-wavelength band radar system with height effectivity and informativity of radiolocation receiving, with the capability of fast moving and deploying is review in this article. The proposed radar system allows to provide measuring coordinates of an aircraft in 3D space, large distance detection, tracking and targeting of all types of aircrafts (including stealth aircrafts), carry out integral processing of radiolocation information, ELINT, EM analysis, as well as jamming and clatter canceling.